Vasculitis in a case of rupioid syphilis in HIV. Issue 3 (4th May 2022) - Rodriguez, Connor; Dhaliwal, Parneet; Readinger, Allison
Abstract: Secondary syphilis can present with a diffuse, nonpruritic, contagious skin rash. The most common presentation of the rash consists of reddish-brown macules and papules seen on the palms and soles, often with papules and plaques on the torso and proximal extremities. However, the presentation may also include warty or raised mucous membrane lesions or patchy alopecia. In this case, we present a patient with rupioid syphilis, an atypical cutaneous manifestation of malignant secondary syphilis. Further, this case illustrates atypical biopsy findings in patients with rupioid syphilis. The variety of cutaneous and histologic presentations in secondary syphilis can make it challenging to identify the cause of the rash.